Report: Forensic Examination and Medicolegal Aspects in A Case of Death by Hanging - Tutik Purwanti; I Nyoman Restu Ananta Wibawa; Putu Bagaskara Surya Permana Mahindra Putra; Ni Made Irma Yanti; Gde Mahesa Deva Setiawan; Ni Putu Rahma Priyastika Dewi; Ni Putu Ananda Gita Prasanthi (International Journal of Health Engineering and Technology, 2025)
Abstract: Background: Suicide is a serious global health problem, with hanging being the most dominant method, including in Indonesia. Hanging causes asphyxia through airway obstruction, vascular compression, and vagus nerve stimulation. Risk factors include mental disorders, substance abuse, socioeconomic stress, and family problems. Clinical, forensic, and epidemiological studies are crucial to differentiate hanging from other forms of asphyxia and to develop effective prevention strategies to reduce mortality rates. Case Description: We report a case of death by hanging involving a 20-year-old woman. In this case, it is suspected that the victim's actions were motivated by psychological pressure that influenced her thoughts to end her life. The victim hanged herself using a scarf that she owned and did so in the ventilation of the bathroom door. Signs of suicide were also reinforced by the discovery of previous suicide attempts, in the form of incised wounds on the victim's lower arms and thighs. Ligature marks were found in the form of abrasions that crossed obliquely across the front of the victim's neck. The hanging was carried out by complete hanging because the victim's entire body was hanging freely. Based on the location of the knot, this case is classified as a typical hanging because the knot was located behind the neck. The possible mechanism of death was compression of the blood vessels and asphyxia. Conclusion: Death by hanging is a frequently reported form of suicide and is influenced by psychological and socioeconomic factors. Medicolegal forensic examination helps determine the mechanism and cause of death, which in cases of hanging is usually caused by compression of the neck blood vessels due to the ligature.